Under pressure - A historical vignette on surgical timing in traumatic spinal cord injury - Paula Valerie ter Wengel; Florence Reith; Charlotte Y. Adegeest; Michael G. Fehlings; Brian K. Kwon; W. Peter Vandertop; Cumhur F. Öner (Brain and Spine)
Introduction: It was not even a century ago when a spinal cord injury (SCI) would inevitably result in a fatal outcome, particularly for those with complete SCI. Throughout history, there have been extensive endeavours to change the prospects for SCI patients by performing surgery, even though many believed that there was no way to alter the catastrophic course of SCI. To this day, the debate regarding the efficacy of surgery in improving the neurological outcome for SCI patients persists, along with discussions about the timing of surgical intervention. Research question: How have the historical surgical results shaped our perspective on the surgical treatment of SCI? Material and methods: Narrative literature review. Results: Throughout history there have been multiple surgical attempts to alter the course of SCI, with conflicting results. While studies suggest a potential link between timing of surgery and neurological recovery, the exact impact of immediate surgery on individual cases remains ambiguous. It is becoming more evident that, alongside surgical intervention, factors specific to both the patient and their surgical treatment will significantly influence neurological recovery. Conclusion: Although a growing number of studies indicates a potential correlation of surgical timing and neurological outcome, the precise influence of urgent surgery on an individual basis remains uncertain. It is increasingly apparent that, despite surgery, patient- and treatment-specific factors will also play a role in determining the neurological outcome. Notably, these very factors have influenced the results in previous studies and our views concerning surgical timing.